Spontaneous rupture of an arachnoid cyst combined with chronic subdural hematoma: a case report and review of the literature - Zhang, Jinwen; Han, Bing; Wang, Zengwu; Sun, Fenglei; Liu, Naizheng (Frontiers in Surgery, 2025)
This case report discusses a 16-year-old male with a previously diagnosed left fronto-temporo-parietal arachnoid cyst (AC) who developed progressively worsening intermittent headaches. Magnetic resonance imaging (MRI) revealed a spontaneous chronic subdural hematoma (CSDH), despite no history of trauma or bleeding disorders. The cyst, discovered incidentally three years prior, had been asymptomatic until this event; hence, no interval cranial computed tomography (CT) or MR imaging was performed. The patient underwent burr-hole irrigation and drainage under general anaesthesia. Postoperative scans confirmed complete resolution of the hematoma and a significant reduction in the cyst size, with no recurrence of the cyst at the six-month follow-up. This case, supported by a systematic review of 28 recent studies (2020–2025), highlights that AC can spontaneously rupture, leading to CSDH. Burr-hole irrigation surgery proves to be a safe and efficient intervention, emphasizing the need for long-term monitoring in AC patients to manage potential hemorrhagic complications promptly.